2017
DOI: 10.5194/angeo-35-839-2017
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization effect on trends in sunshine duration in China

Abstract: Abstract. There is an ongoing debate on whether the observed decadal variations in surface solar radiation, known as "dimming" and "brightening" periods, are a large-scale or solely local phenomenon. We investigated this issue using long-term sunshine duration records from China, which experienced a rapid increase in urbanization during the past decades. Over the period 1960-2013, 172 pairs of urban and nearby rural stations were analyzed. Urban and rural sunshine duration trends show similar spatial patterns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 54 publications
(74 reference statements)
2
34
0
Order By: Relevance
“…As seen from Figure 7d, surface-observed TCC keeps increasing during 1993-2015 with an even stronger increase in the latter period, which could not explain the increase in SSR. An increasing trend in TCC since the 1990s is also evidenced over China by Xia [68], Liu et al [69], and Wang et al [5]. Changes in satellite-derived CLARA-A2 SSR are generally in good agreement with the trends of CFC used in CLARA-A2 (Figure 7b,e), suggesting a good representation of cloud effects in the satellite-retrieved SSR, as expected from the satellite-retrievals.…”
Section: A Case Study Of Beijingsupporting
confidence: 70%
See 1 more Smart Citation
“…As seen from Figure 7d, surface-observed TCC keeps increasing during 1993-2015 with an even stronger increase in the latter period, which could not explain the increase in SSR. An increasing trend in TCC since the 1990s is also evidenced over China by Xia [68], Liu et al [69], and Wang et al [5]. Changes in satellite-derived CLARA-A2 SSR are generally in good agreement with the trends of CFC used in CLARA-A2 (Figure 7b,e), suggesting a good representation of cloud effects in the satellite-retrieved SSR, as expected from the satellite-retrievals.…”
Section: A Case Study Of Beijingsupporting
confidence: 70%
“…Hence, its impacts can reach far beyond the territory of China and affect global climate and living organisms [3,4]. Almost no regulations were imposed on air pollution in China before the 1980s [5]. The first official document aiming at improving ambient air quality in China was the National Ambient Air Quality Standards, originally formulated in 1982 [6].…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, it is argued that the decrease may be related to the increase in cloud cover. In addition, several studies have reported a correlation between a decrease in sunshine duration and urbanization [84]. Recently, Wei Pan [85] reported that the number of haze days significantly increased in North China (including in the HRB).…”
Section: Discussionmentioning
confidence: 99%
“…For the whole of China covering over 9.6 million km 2 , there are only 130 solar radiation stations, only 59 of them with records covering more than 75% of the measurement period from 1957 to the present. In addition, around three quarters of the stations are located in urban areas, indicating a non-negligible urbanization effect on the derived trends in China [13]. To compensate for the limited spatial representation of ground observations, one effective alternative has been offered by satellite products due to their unique geographical coverage and high spatial resolution [14][15][16].…”
Section: Introductionmentioning
confidence: 99%